CDC ROADM design tradeoffs due to physical layer impairments in optical networks - Sequeira, D. G.; Cancela, L.; Rebola, J. (Optical Fiber Technology, 2021)
In this work, we assess the impact of several physical layer impairments (PLIs) on the performance of optical networks based on colorless, directionless and contentionless reconfigurable optical add/drop multiplexers (ROADMs), through Monte-Carlo simulation, and considering polarization division multiplexing 4 and 16 quadrature amplitude modulation (QAM) signals, at 28 GBaud, for 37.5 GHz optical channels. The PLIs taken into account are the amplified spontaneous emission noise, optical filtering, in-band crosstalk and nonlinear interference noise caused by Kerr effect. A detailed model of the ROADM node is built considering two typical ROADM architectures, broadcast and select (B&S) and route and select (R&S), and two different add/drop structures, multicast switches (MCSs) and wavelength selective switches (WSSs), resulting in four different ROADM node scenarios. Our results have shown that for 16QAM signals, the B&S ROADMs with WSSs-based add/drop structures is the scenario that has the best relation cost/performance, foreseeing its use in metro networks, while for 4QAM signals, the R&S ROADM with WSSs-based add/drop structure scenario allows a larger ROADM cascade at an expectable lower cost anticipating its implementation in long-haul networks.